A2 3 Ice to Melt You: Ice Cube Solutions to Global Warming - Dyer, Thomas; Lewis, Dan; Scrivener, Callum (Physics Special Topics, 2024)
We set out to determine the amount of ice needed to cool the oceans to pre-Industrial Revolution levels from the perspective of Earth in 2100, where oceans have warmed by 1.2◦C, using the method outlined in the Futurama episode “Crimes of the Hot”. We determined it would require 5.366 × 1017 kg of ice to cool the oceans, approximately 2% of the Antarctic Ice Sheet. This ice melting would cool the oceans, but also raise sea levels by 1.5 metres, flooding many low-lying cities, proving catastrophic for humanity.